Blood lipid spectrum and elastic properties of arteries in patients with chronic pancreatitis in combination with arterial hypertension - A.Yu. Filippova; M. Löhr; V.V. Kryvoshei (Medičnì Perspektivi, 2022)
110 patients aged 45-65 years with chronic pancreatitis were examined. The first group consisted of patients with a combined course of chronic pancreatitis with arterial hypertension; the second group - patients with chronic pancreatitis without concomitant hypertension. All patients were examined for total cholesterol, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and very low-density lipoprotein cholesterol. Arterial stiffness was determined by the pulse wave velocity. It was found that patients of the 1st group had significantly higher levels of triglycerides (37.2%), low-density lipoprotein cholesterol (13%), total cholesterol (25%), atherogenic ratio (19.6%) and significantly lower levels of high-density lipoprotein cholesterol (15.4%). Correlations between age and the level of atherogenic ratio, low-density lipoprotein cholesterol were established – r=0.35; p<0.01; r=0.37; p<0.01, respectively. The duration of chronic pancreatitis positively correlated with the level of triglycerides, low-density lipoprotein cholesterol – r=0.43; p<0.01; r=0.34; p<0.01, respectively. The level of brachial artery augmentation index was significantly lower by 43% in patients with chronic pancreatitis in combination with arterial hypertension, while the aortic augmentation index was significantly higher by 37.6% (p<0.01). It was found that patients of the 1st group had a significantly higher pulse wave velocity in the carotid-femoral segment compared to the 2nd group – by 7.5% (p<0.01). Significant correlations have been established between the brachial artery augmentation index and age, total cholesterol, atherogenic ratio, high and low density lipoprotein cholesterol, triglycerides, cardiovascular risk level by the SCORE scale in patients with a combined course of chronic pancreatitis with arterial hypertension. Conclusions. Patients with the combination of chronic pancreatitis and hypertension had significantly higher levels of triglycerides, low-density lipoprotein cholesterol and total cholesterol. Changes in the elastic properties of arteries in patients with chronic pancreatitis with comorbid hypertension were characterized by an increase in the augmentation index and the pulse wave velocity in the carotid-femoral segment.